Decoding Islamic Aesthetics: A Semiotic Study of Calligraphy and Ornaments in Al-Munawwarah Mosque, Batu Bara - Fauziah, Fauziah (Medan Resource Center, 2025)
This study explores the semiotic meanings embedded in the calligraphy and ornamental designs of the Al-Munawwarah Mosque in Batu Bara through Ferdinand de Saussure’s theoretical lens, particularly the concepts of signifier and signified. The research seeks to identify the types and forms of visual elements used and interpret their symbolic meanings within a cultural and religious context. Employing a qualitative descriptive method, data were collected through direct observation, in-depth interviews with mosque leaders and cultural figures, and visual documentation of architectural features. The findings reveal the use of four calligraphic styles—thuluth, diwani, naskhi, and kufi—and two dominant ornamental motifs: Malay floral patterns with vibrant colors and Arabic geometric designs characterized by repetition and symmetry. These elements collectively serve as cultural and theological signifiers that construct a local Islamic aesthetic. The study concludes that the calligraphy and ornaments function not merely as decorative art but as a visual semiotic system that conveys spiritual identity and communal values. While the analysis is limited by restricted access to official design documents, the study offers a foundational perspective for understanding how Islamic architectural elements communicate meaning, thereby inviting further comparative research in regional mosque aesthetics.